Loss-of-Function in SMAD4 Might Not Be Critical for Human Natural Killer Cell Responsiveness to TGF-β - Healy, Lachlan P.; Rossi, Gustavo R.; Rautela, Jai; Slade, Charlotte A.; Huntington, Nicholas D.; Winship, Ingrid M.; Souza-Fonseca-Guimaraes, Fernando (Frontiers in Immunology, 2019)
We characterized the NK cell phenotype and function in three family members with Hereditary Hemorrhagic Telangiectasia (HHT) due to heterozygous SMAD4 mutations. Loss-of-function mutation in this gene did not induce developmental effects to alter CD56bright or CD56dim NK cell subset proportions in peripheral blood; and did not result in major differences in either their IL-15-induced proliferation, or their cytokine secretion response to TGF-beta1. These data suggest that SMAD4 plays a redundant role in downstream TGF-beta signaling in NK cells.